1990
DOI: 10.1172/jci114900
|View full text |Cite
|
Sign up to set email alerts
|

Insulin regulates apolipoprotein B turnover and phosphorylation in rat hepatocytes.

Abstract: Our laboratory has previously shown that insulin inhibits the secretion of newly-synthesized and immunoreactive apo B from rat hepatocytes. We have also shown that apo B is secreted as a phosphoprotein and that phosphorylation is increased in hypoinsulinemic nonketotic diabetes. The present studies were conducted to determine whether the ability of insulin to inhibit apo B secretion is related to alterations in apo B turnover and whether insulin itself affects apo B phosphorylation. Pulsechase studies with I35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
2
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 32 publications
0
33
2
2
Order By: Relevance
“…44 In the present study, the regulation of VLDL apoB secretion appeared to be closely linked with hyperinsulinaemia. Recent in vitro 14,15 and in vivo 16,17 studies have demonstrated that acute hyperinsulinaemia decreases the hepatic secretion of VLDL apoB in the nondiabetic state. By contrast, studies using rat livers VLDL apoB secretion in men with visceral obesity FM Riches et al have shown that in the long-term, insulin stimulates VLDL apoB secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 In the present study, the regulation of VLDL apoB secretion appeared to be closely linked with hyperinsulinaemia. Recent in vitro 14,15 and in vivo 16,17 studies have demonstrated that acute hyperinsulinaemia decreases the hepatic secretion of VLDL apoB in the nondiabetic state. By contrast, studies using rat livers VLDL apoB secretion in men with visceral obesity FM Riches et al have shown that in the long-term, insulin stimulates VLDL apoB secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies suggest that the hepatic secretion of VLDL apoB is dependent on the availability of free fatty acids that determine the synthetic rates of both cholesterol esters and triglycerides. 11,13 Both in vitro 14,15 and in vivo 16,17 studies have shown that insulin inhibits the hepatic secretion of VLDL apoB. In vivo data have also shown that enhanced cholesterol synthesis is a feature of insulin resistance 18 and that acute hyperinsulinaemia diminishes the rate of cholesterogenesis as measured by the plasma concentration of mevalonic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Apo B gene defects have been ruled out by linkage analysis in FCH kindreds (40). Several studies have demonstrated that insulin decreases apo B secretion in vitro by enhanced intracellular degradation (41)(42)(43)(44). However, the hyperinsulinemia in FCH may be a consequence of the insulin resistance and this may be associated to impaired metabolism of fatty acids by peripheral cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, whereas experiments conducted with isolated perfused rat liver showed that insulin stimulates both synthesis and secretion of TAG [136,137], many subsequent studies conducted on cultured hepatocytes have found that insulin, although promoting synthesis of TAG, inhibits its secretion [6,8,133,138,139]. The reasons for this discrepancy between the two sets of data may reside in the use of different experimental systems (perfused liver, cultured cells) and in the choice of the precise perfusion or culture conditions, by different laboratories.…”
Section: Experimental Observations For a Role Of Insulin In Tag Secrementioning
confidence: 99%
“…In addition, it is apparent that TAG synthesis and secretion respond to different concentrations of insulin in cell-culture experiments, higher ones being required to inhibit secretion [8]. There also seems to be disagreement as to whether insulin only affects apoB degradation [139], or whether it also affects apoB synthesis [140]. Moreover, prolonged exposure (5 days) of cultured rat hepatocytes to insulin enhanced apoB %) secretion by promoting apoB mRNA editing [141].…”
Section: Experimental Observations For a Role Of Insulin In Tag Secrementioning
confidence: 99%